Aesthetic and philosophical reflections on mood : Stimmung and modernity - Breidenbach, Birgit (New York, NY : Routledge, 2020)
This study explores the concept of Stimmung in literary and philosophical texts of the modern age. Signifying both 'mood' and 'attunement', Stimmung speaks to the categories of affective experience and aesthetic design alike. The study locates itself in the nexus between discourses on modernity, existentialism and aesthetics and uncovers the pivotal role of Stimmung in 19th- and 20th-century European narrative fiction and continental philosophy. The study first explores the philosophical and aesthetic origins and implications of Stimmung to, then, discuss its role in the narrative fiction of three key authors of modern literature: Fyodor Dostoevsky, Samuel Beckett and Thomas Bernhard. These readings demonstrate a significant shift towards an aesthetic of affective intensity and immediacy, in which the experience of the reading process takes centre stage as each author develops an aesthetic philosophy of Stimmung in their own right. Through its focus on the concept of Stimmung, the study thus unearths a fundamental link between existentialist concerns and narrative practice in modern literature.
PrefaceIntroduction. Stimmung and Modernity: Theoretical ExplorationsStimmung in Modern PhilosophyConceptualising Stimmung in LiteratureChapter 1: Fyodor Dostoevsky's Moody ModernityAlienation in the Modern CityThe Intensity of Aesthetic ExperienceAesthetic Intensity and the Modern ConditionChapter 2: Aesthetic Attunement in Samuel Beckett's Narrative FictionThe (Pre- and Post-)Cartesian Subject in Murphy and Watt'All I am is feeling:' The Textual Dynamics of MolloyDecomposed Selves, Voices in the DarkChapter 3: Eine 'Stimmungssache:' Thomas Bernhard's 'Trilogy of the Arts'Music and Artistic Ideal in The LoserWoodcutters: Irritation and the Creative ProcessBernhard's Aesthetics of Stimmung and the Failure of Art in Old MastersConclusionBibliography
OCLC-licensed vendor bibliographic record.
Keywords: Mood (Psychology) in literature